C11orf58 (Hero20) Gene Polymorphism: Contribution to Ischemic Stroke Risk and Interactions with Other Heat-Resistant Obscure Chaperones - Irina Shilenok; Ksenia Kobzeva; Vladislav Soldatov; Alexey Deykin; Olga Bushueva (Biomedicines)
Background: Recently identified Hero proteins, which possess chaperone-like functions, are promising candidates for research into atherosclerosis-related diseases, including ischemic stroke (IS). Methods: 2204 Russian subjects (917 IS patients and 1287 controls) were genotyped for fifteen common SNPs in Hero20 gene C11orf58 using probe-based PCR and the MassArray-4 system. Results: Six C11orf58 SNPs were significantly associated with an increased risk of IS in the overall group (OG) and significantly modified by smoking (SMK) and low fruit/vegetable intake (LFVI): rs10766342 (effect allele (EA) A; P(OG = 0.02; SMK = 0.009; LFVI = 0.04)), rs11024032 (EA T; P(OG = 0.01; SMK = 0.01; LFVI = 0.036)), rs11826990 (EA G; P(OG = 0.007; SMK = 0.004; LFVI = 0.03)), rs3203295 (EA C; P(OG = 0.016; SMK = 0.01; LFVI = 0.04)), rs10832676 (EA G; P(OG = 0.006; SMK = 0.002; LFVI = 0.01)), rs4757429 (EA T; P(OG = 0.02; SMK = 0.04; LFVI = 0.04)). The top ten intergenic interactions of Hero genes (two-, three-, and four-locus models) involved exclusively polymorphic loci of C11orf58 and C19orf53 and were characterized by synergic and additive (independent) effects between SNPs. Conclusions: Thus, C11orf58 gene polymorphism represents a major risk factor for IS. Bioinformatic analysis showed the involvement of C11orf58 SNPs in molecular mechanisms of IS mediated by their role in the regulation of redox homeostasis, inflammation, vascular remodeling, apoptosis, vasculogenesis, neurogenesis, lipid metabolism, proteostasis, hypoxia, cell signaling, and stress response. In terms of intergenic interactions, C11orf58 interacts most closely with C19orf53.